(untitled) (Fiep Bulletin - online, 2013)
This study aimed toinvestigate the ability ofdeaf peopleto dance tothe silence,trying to identifyhowsounds are perceivedby them, trying to seehowdeafdevelop yourrhythm andbody awarenessindancing, check alsoa positive influence onthe dancing bodyand emotional developmentof thesepeople who are tryingto observe theintegration ofdeaf people ina group of listenersto dance andanalyzethe benefits ofphysical activitythedeaf student. Made froma qualitative approachwas usedonly onemaleparticipant, age 19. At the beginning, we conducted a literature search ondancedanceDeafanddisability, which served to deepenthe themes andsettings forsolutions.As acollection tool, an intervention was performedthrough danceand thenasemi-structured interview. The results showedthat dancefor the Deafhas a key roleincommunication throughhis body.The same candancethroughvibrations andbodily expressionsof the people aroundyou.This modeof theirmany advantages, such as self-esteem,self-image,self-image andself-confidence, which are essential forthe development andpsychic bodyof every human being.It is therefore essentialthatfurther studies areperformeddances forthe hearing impaired.Therefore, werecommend that youinvest in shareswith other researchin dancefor the Deaf, which extend in differentage groups.